Sustainable utilization of waste carbon black in alkali-activated mortar production - Mohammad R. Irshidat (8047913) (2021)
This article investigates the potential utilization of waste carbon black (WCB) resulting from the aluminum industry as a by-product material in the fly ash-based geopolymer composites production. Experimental study was conducted to evaluate the effect of WCB on the performance of the geopolymer. Different contents of WCB including 5%, 10%, 15%, 20%, 30%, and 40%,by weight of the fly ash, have been incorporated in the geopolymer mix as either additives or fly ash replacement. Life cycle assessment (LCA) has also been conducted to evaluate the landfills utilization and the environmental impact of the WCB incorporation. The experimental results reflected that the WCB could be used as additives in small quantities (5% of fly ash weight) to the geopolymer mix without negatively affecting its performance. Adding 5% of WCB insignificantly enhanced the compressive strength of the geopolymer by 5%, increased its workability and density by 3% and 4%, respectively, and did not affect its excellent thermal stability. Scanning electron microscopic (SEM) imaging showed more unreacted fly ash particles combined with more voids and cracks within the microstructure of the geopolymer with high WCB content. Finally, incorporating WCB in the geopolymer production improved the utilization of landfills use and reduced the global warming potential, acidification potential, eutrophication potential and abiotic depletion potential. Other Information Published in: Case Studies in Construction Materials License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cscm.2021.e00743